The Ron receptor tyrosine kinase activates c-Abl to promote cell proliferation through tyrosine phosphorylation of PCNA in breast cancer - Zhao, Huajun (2013)
Multiple growth pathways lead to enhanced proliferation in malignant cells. However, how the core machinery of DNA replication is regulated by growth signaling remains largely unclear. The sliding clamp PCNA (Proliferating Cell Nuclear Antigen) is an indispensable component of the DNA machinery responsible for replicating the genome and maintaining genomic integrity. We previously reported that epidermal growth factor receptor (EGFR) triggered tyrosine 211 (Y211) phosphorylation of PCNA, which in turn stabilized PCNA on chromatin to promote cell proliferation. Here we show that the phosphorylation can also be catalyzed by the non-receptor tyrosine kinase c-Abl. We further demonstrate that, in the absence of EGFR, signaling to PCNA can be attained through the activation of the Ron receptor tyrosine kinase and the downstream non-receptor tyrosine kinase c-Abl. We show that Ron and c-Abl form a complex, and that activation of Ron by its ligand, HGFL, stimulates c-Abl kinase activity, which in turn directly phosphorylates PCNA at Y211 and leads to an increased level of chromatin-associated PCNA. Correspondingly, HGFL-induced Ron activation resulted in Y211 phosphorylation of PCNA while silencing of c-Abl blocked this effect. We show that cAbl and Y211 phosphorylation of PCNA is an important axis downstream of Ron, which is required for cell proliferation. Treatment with a specific peptide which inhibits Y211 phosphorylation of PCNA or with the c-Abl pharmacological inhibitor imatinib suppressed HGFL-induced cell proliferation. Our findings identify the pathway of Ron-cAbl-PCNA as a mechanism of oncogene-induced cell proliferation, with potentially important implications for development of combination therapy of breast cancer.